BOLA KERANJANG SEBAGAI ALTERNATIF PEMBELAJARAN PENDIDIKAN JASMANI DISEKOLAH MENENGAH - Lilik Indriharta (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2006)
Korfball are the only game that involved man and women on each team. Nowadays peopleleft Korfball games as a sport in the high school. Although it offers many advantages: it’scheap, easy to play, simple equipment, and entertaining. High school age is a puberty age,a period in search of identity include they start to falling in love. Therefore, this game isgiving an appropriate timing to teach it in the high school. As a sport, Korfball requireddiscipline, teamwork, manners, sportsmanship and physical fitness. Therefore, sport teachercan use Korfball as alternative.Keyword: Bola Keranjang, Sport lesson.